Characteristics of successful expansion of tumor-infiltrating lymphocytes from colorectal cancer liver metastasis - Jina Baek; Gyuheon Choi; GunHee Lee; Hyun Lee; Gyungyub Gong; Hye Seon Park; Chae-Lyul Lim; Joo Young Kim; Hee Jin Lee (Scientific Reports)
Abstract Adoptive cell therapy (ACT) utilizing tumor-infiltrating lymphocytes (TILs) has emerged as a successful treatment modality for various malignancies. However, TILs cultured from colorectal cancer (CRC) liver metastasis remain underexplored. Fifteen CRC liver metastasis tissues underwent initial expansion (IE) of TILs and rapid expansion (REP). Histologic examination including the level of stromal TILs and Klintrup-Mäkinen score, were assessed by pathologists and deep learning-derived spatial analysis. We performed correlation analysis between expanded TILs and histopathologic factors. All cases exhibited successful IE, with a mean IE TIL count per fragment and total IE TIL per case of 2.59 ± 2.79e5 cells and 167.79 ± 126.97e5 cells, respectively. Five cases underwent REP, with a median fold change of 3,610 (range, 1,136–4,925). The median CD4+/CD8 + ratio in IE TILs and REP TILs were 3.66 and 0.68, respectively. A significant correlation was observed between the mean number of expanded TILs per fragment and KM score (p = 0.022). Successful expansion of TILs from CRC liver metastasis was achieved. Assessment of KM score may serve as a predictive tool for the obtainable TILs before IE. These findings lay the groundwork for future studies to establish effective ACT in patients with metastatic CRC.